2013
DOI: 10.4093/dmj.2013.37.4.270
|View full text |Cite
|
Sign up to set email alerts
|

Association of Estrogen Receptor α GenesPvuII andXbaI Polymorphisms with Type 2 Diabetes Mellitus in the Inpatient Population of a Hospital in Southern Iran

Abstract: BackgroundEstrogen plays a fundamental role in the pathogenesis of type 2 diabetes mellitus (T2DM). Very few studies have shown the association between estrogen receptor α (ERα), PvuII and XbaI gene polymorphisms with T2DM in both men and women. We evaluated the hypothesis that PvuII and XbaI polymorphisms of ERα gene may be associated with T2DM in adult.MethodsFrom spring of 2010 to the fall of 2011, a case-control study was performed at clinical centers of Jahrom University of Medical Sciences. We included 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Our study was in agreement with the last one as lipid profile assay shows a significant increase among patients group who carry C allele in the homozygous or heterozygous form (CC or TC genotypes) as there was a highly significant increase in triglycerides, total cholesterol and LDL-C while there was a highly significant decrease in the level of HDL-C, that high serum lipid can increase the risk of T2DM in healthy group ( Mohammadi et al, 2013 ). These results may explain several studies which have shown a positive relationship of ESRα PvuII C allele with a higher risk of atherosclerosis and stroke in men ( Lehtimäki et al, 2002; Shearman et al, 2005 ) and familial hypercholesterolemia ( Lu et al, 2002 ) as ESR-α can indirectly influence many molecular signaling mechanisms related to risk factors for cardiovascular disease (CVD) via co-modulation with important factors such as insulin receptor, insulin-like growth factor receptor, and peroxisome proliferator-activated receptor ( Casazza et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our study was in agreement with the last one as lipid profile assay shows a significant increase among patients group who carry C allele in the homozygous or heterozygous form (CC or TC genotypes) as there was a highly significant increase in triglycerides, total cholesterol and LDL-C while there was a highly significant decrease in the level of HDL-C, that high serum lipid can increase the risk of T2DM in healthy group ( Mohammadi et al, 2013 ). These results may explain several studies which have shown a positive relationship of ESRα PvuII C allele with a higher risk of atherosclerosis and stroke in men ( Lehtimäki et al, 2002; Shearman et al, 2005 ) and familial hypercholesterolemia ( Lu et al, 2002 ) as ESR-α can indirectly influence many molecular signaling mechanisms related to risk factors for cardiovascular disease (CVD) via co-modulation with important factors such as insulin receptor, insulin-like growth factor receptor, and peroxisome proliferator-activated receptor ( Casazza et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…In this subgroup 42 studies were assessed and all of them were designed as case control association studies [ 22 , 35 – 68 , 70 – 75 ] except for one which was cross sectionally designed [ 69 ]. In 33 studies, PCR- RFLP was used for genotyping [ 22 , 36 – 38 , 40 54 , 56 , 58 61 , 63 – 66 , 69 , 72 – 75 ]. In 5 of them PCR was used [ 35 , 57 , 62 , 70 , 71 ] and the remaining studies PCR-SCA [ 39 ], real-time PCR [ 55 ], ARMS-PCR [ 66 ], Gap PCR [ 67 ], and CSGE (conformation-sensitive gel electrophoresis) sequencing [ 68 ] as the genotyping method were applied.…”
Section: Resultsmentioning
confidence: 99%
“…Association of estrogen receptor α and its Pvu II(PP,Pp,pp) and Xba I(XX,Xx,xx) polymorphism with T2DM in two studies was assessed [ 40 , 49 ]. In one study, the significant association of Pvu II and Xba I polymorphisms with T2DM was observed ( P = 0.014 and P = 0.002, resp.)…”
Section: Resultsmentioning
confidence: 99%
“…After screening titles and abstracts, 33 articles with full-text were retrieved for eligibility. At last, 11 studies were in accordance with the inclusive criteria [16][17][18][19][20][21][22][23][24][25][26]. The detailed process of study selection is presented in ▶ Fig.…”
Section: Literature Research and Study Characteristicsmentioning
confidence: 99%
“…1. Among the included studies, eight studies have investigated the ESR1 gene polymorphisms in patients with T2DM [16][17][18][19][20][21][22][23]. Seven articles including 939 persons with T2DM and 1054 controls studied the PvuII and XbaI polymorphisms [16-20, 22, 23], and one study including 49 T2DM participants and 138 control people only focused on the XbaI polymorphism [21].…”
Section: Literature Research and Study Characteristicsmentioning
confidence: 99%